Особливості адміністративно-правового забезпечення безпеки дорожнього руху підрозділами патрульної поліції в умовах воєнного стану в Україні - Гусаров, С. М.; Gusarov, S. M.; Сергій Гусаров (Європейські перспективи. - 2023. - № 3. - С. 179-185, 2023)
Розглянуто правові засади діяльності Національної поліції України загалом та підрозділів патрульної поліції України в сфері забезпечення безпеки дорожнього руху. Проаналізовано норми законодавчих та інших нормативно-правових актів України, відповідно до яких було значно розширено повноваження поліції у сфері забезпечення безпеки дорожнього руху на період дії в Україні воєнного стану. Особливу увагу приділено змінам і доповненням, що внесені у Закон України «Про Національну поліцію» щодо врегулювання порядку застосування превентивних поліцейських заходів та заходів примусу в процесі забезпечення поліцією безпеки дорожнього руху.

The article examines the legal principles of the National Police of Ukraine in general and units of the Patrol Police of Ukraine in the field of road safety. The norms of legislative and other normative legal acts of Ukraine were analyzed, according to which the powers of the police in the field of ensuring road traffic safety were significantly expanded during the period of martial law in Ukraine. Special attention was paid to the changes and additions made to the Law of Ukraine «On the National Police» regarding the regulation of the procedure for applying preventive police measures and coercive measures in the process of ensuring traffic safety by the police. It was concluded that the patrol police in the structure of the National Police units is the main subject of ensuring road safety in the country, despite the fact that the administrative and legal principles of police activity in the conditions of martial law in Ukraine have undergone significant changes. It is noted that the significantly expanded powers of patrol police officers in the field of ensuring road traffic safety in Ukraine should be recognized as a key feature of patrol police activities under martial law. It was emphasized that achieving a positive result in the field of ensuring road traffic safety is possible not only on the condition of improving the current regulatory and legal framework that regulates the activities of the patrol police, but also on the awareness of each police officer of the need for the systematic application of effective measures to ensure road traffic safety, the importance of preventive work in relation to preventing violations of traffic rules, improving one’s own professional skills during the application of police measures.

Рассмотрены правовые основы деятельности Национальной полиции Украины и подразделений патрульной полиции Украины в сфере обеспечение безопасности дорожного движения. Проанализированы нормы законодательных и других нормативно-правовых актов Украины, в соответствии которых были значительно расширены полномочия полиции в сфере обеспечения безопасности дорожного движения на период действия в Украине военного положения.
Keywords: Національна поліція України; National Police of Ukraine; Национальная полиция Украины; патрульна поліція; patrol police; патрульная полиция; забезпечення безпеки дорожнього руху; ensuring road traffic safety; обеспечение безопасности дорожного движения; адміністративно-правове забезпечення; administrative and legal support; административно-правовое обеспечение; воєнний стан; martial law; военное положение; поліцейські заходи; police measures; полицейские мероприятия; адміністративна відповідальність; administrative responsibility; административная ответственность